2019
DOI: 10.2478/cerce-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

Post-Harvest Losses along the Rice Value Chain in Kwara State, Nigeria: An Assessment of Magnitude and Determinants

Abstract: Post-harvest losses, particularly along the rice value chain, have been highlighted as a major source of reduction in revenue among the value chain actors. It is therefore imperative that empirical assessment of the magnitude and determinants be investigated, so as to be able to provide a reliable policy stand that can help reduce these losses. Patigi and Edu local government areas were purposively sampled from Kwara state, Nigeria, since they are the major producers of rice in the State. Data were gathered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…Majority (57.5%) of the respondents had no formal education. This is in line with Babatunde (2019) result that stated that majority of the processors in the study area have no formal education. This is an indication that most of the processors are uneducated.…”
Section: Socio-economics Characteristics Of Local Rice Processors In ...supporting
confidence: 91%
“…Majority (57.5%) of the respondents had no formal education. This is in line with Babatunde (2019) result that stated that majority of the processors in the study area have no formal education. This is an indication that most of the processors are uneducated.…”
Section: Socio-economics Characteristics Of Local Rice Processors In ...supporting
confidence: 91%
“…Postharvest losses in rice may be quantitative or qualitative. Quantitative losses result in weight or volume reduction in the potential yield, while qualitative losses result in a reduction in the value of the usable rice owing to physical and chemical changes, such as poor appearance, poor taste, and unpleasant odor [35]. Nonetheless, harvest losses are usually measured as actual physical losses (i.e., quantitative losses).…”
Section: Estimation Methodsmentioning
confidence: 99%
“…As one of the world's three leading food crops, rice feeds almost half of the world's population, making it the most consumed cereal grain [33], especially in low-and lowermiddle-income countries [34]. Among rice farmers, processors, and marketers, rice farmers experience the highest loss [35,36]. Losses on farms reduce farmers' incomes, and for farmers in low-income countries living on the edge of hunger, these losses are closely associated with food insecurity [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Babatunde et al (2019) reported that household size and farm size are the determinants of food losses in rice production. We see that all significant constraints have a negative impact on losses.…”
Section: Determination Of the Effect Of The Constraints On Food Lossesmentioning
confidence: 99%